Military news at Hassan Bin Mohamed El-bourini writing biographies of Notables waqt - Shukairat, Hussein Raja (Journal of Humanities & Social Sciences, 2018)
Summary this study aims to follow military news and military when Hassan Bin Mohamed El-bourini writing biographies of objects, the study began with balborini definition in terms of his birth and early life to the definition and briefly with the ageing and his marriage and his trips, culture and exciting and his approach to writing translations. Then expanded the study to follow news of the military and the soldiers when bourini whether directly or news came came through from translate bourini, the study concluded that his bourini from information on the movement of alskbanet and other outlaw movements of the Ottoman Empire is considered one of the most important books on These particular topics and value of the information derived from the mantle and person without her, as the names of the table was installed translate bourini who linked to the military, telling them, this table at the end of the study and a summary of news items in each translation table preceded the finale outlined what study Concisely.